Nutritional and Physiological Functions of Amino Acids in Pigs - Blachier, Francois; Wu, Guoyao; Yin, Yulong; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
This book provides developmental data regarding piglets (with a focus on the gastrointestinal tract), data related to amino acid metabolism in pigs, data related to nutritional and physiological functions of amino acids in pigs, nutritional requirements for amino acids in pigs, signaling roles of amino acids, methodological aspects in amino acid research and the pig model for studying amino acid-related human diseases.
Introduction -- Anatomical characteristics of the gastrointestinal tract and digestive glands of pigs during development -- Development of the gastrointestinal tract in pigs -- Development of the digestive glands in pigs -- Development and renewal of the intestinal villi in pigs -- Terminal digestion, amino acid absorption/metabolism and microbiota in the pig intestine during development -- Terminal digestion of polypeptides and amino acid absorption by the pig intestine epithelial cells during development -- Developmental amino acid metabolism in the pig small and large intestine epithelial cells -- Development of the micro-ecological system in small and large intestine of piglets -- Physiological functions of amino acids in pigs -- Structure and functions of amino acids: an overview -- Synthesis and degradation of proteins in pigs -- Factors that affect amino acid metabolism in pigs -- Amino acids and hormone secretion in pigs -- Amino acids, gene expression and cell signaling in the pig intestine -- Amino acids and immune functions -- Amino acids and obesity, diabetes and dyslipidemia -- Methodology for research on amino acid -- Methods for amino acid analysis -- Surgical techniques used for research in amino acid nutrition -- Measurement of protein digestibility in pigs -- Measurement of synthesis and degradation of proteins -- Methods for measuring amino acids of endogenous origin in pig intestines.
Keywords: Life sciences; Food science; Veterinary medicine; Animal Physiology; Life Sciences; Animal Physiology; Veterinary Medicine; Food Science